Blockchain Technology for Enhancing Transparency and Accountability in Educational Administration - Chevi Herli Sumerli A; Adam Mudinillah; Bouyea Jonathan; Nurul Giswi Karomah; Noor Fazariah Handayani (Journal of Social Science Utilizing Technology, 2024)
Background. Educational institutions face increasing demands for transparency and accountability in their administrative processes. Traditional systems often lack the necessary security, efficiency, and transparency to meet these demands, leading to issues such as fraud, mismanagement, and mistrust. Blockchain technology, known for its decentralized and immutable nature, has emerged as a promising solution to address these challenges within educational administration. Purpose. This research aims to explore the potential of blockchain technology in enhancing transparency and accountability in educational administration. The study focuses on how blockchain can improve data integrity, reduce administrative costs, and streamline processes in educational institutions. Method. A qualitative approach was adopted, involving case studies of institutions that have implemented blockchain-based solutions for administrative purposes. Data was collected through interviews with administrators, technology experts, and stakeholders to assess the impact of blockchain technology on transparency and accountability. Results. The findings indicate that blockchain significantly improves data security and traceability, ensuring that records are tamper-proof and easily auditable. It also reduces administrative overhead by automating processes and streamlining communication between stakeholders. Furthermore, blockchain enhances stakeholder trust through transparent and decentralized decision-making. Conclusion. Blockchain technology holds great promise for revolutionizing educational administration by providing a secure, transparent, and efficient system. Future research should focus on addressing scalability challenges and exploring broader applications of blockchain in educational settings.